Assessment of per- and polyfluoroalkyl substances (PFAS) in the Indian River Lagoon and Atlantic coast of Brevard County, FL, reveals distinct spatial clusters. (August 2022) - Griffin, Emily K.; Aristizabal-Henao, Juan; Timshina, Alina; Ditz, Heather L.; Camacho, Camden G.; da Silva, Bianca F.; Coker, Eric S.; Deliz Quiñones, Katherine Y.; Aufmuth, Joe; Bowden, John A.
Abstract: Per- and polyfluoroalkyl substances (PFAS) constitute a class of highly stable and extensively manufactured anthropogenic chemicals that have been linked to a variety of adverse health effects in humans and wildlife. These compounds are ubiquitously distributed in the environment and have been measured in aquatic systems globally. However, there are limited data on longitudinal comprehensive assessments of PFAS profiles within sensitive aquatic ecosystems. Surface water samples were collected from the Indian River Lagoon (IRL) and the Atlantic coast within Brevard County (BC), FL in December of 2019 (n = 57) and again from corresponding locations in February of 2021 (n = 40). Samples were analyzed by ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) to determine the occurrence, concentration, and distribution of 92 PFAS. No significant difference in total PFAS concentrations were identified between samples collected in 2019 (87 ng/L) and those collected in 2021 (77 ng/L). However, comparisons of PFAS among four natural sub-regions within Brevard County revealed site- and regional-specific differences. The Banana River exhibited the greatest concentration of total PFAS, followed by the southern Indian River, the northern Indian River, and then the Atlantic coast. Six distinct PFAS profiles were identified with the novel application of multivariate statistical cluster analysis, which may be useful for identifying potential sources of PFAS. Elevated total PFAS and unique compound mixtures identified in the Banana River are most likely a result of industrial discharge and extensive historical use of aqueous film-forming foams (AFFF). The environmental persistence of PFAS threatens key ecosystem services and the ecological homeostasis of the Indian River Lagoon – the most biologically diverse estuary in North America. Brevard County offers a unique model site that may be used to investigate potential exposure and health implications for wildlife and adjacent coastal communities, which could be extrapolated to better understand and manage other critical coastal systems. Graphical abstract: Image 1 Highlights: PFAS detected in all surface water samples collected from Brevard County (BC). Greatest levels of PFAS resulted from the Banana River, a segment of the IRL. Novel use of cluster analysis useful for identifying associations of similar PFAS profiles. Distinctive clustering of PFAS in BC suggests multiple sources of contamination. Maximum ∑PFAS from single sample (265 ng/L) greatly exceeds EPA drinking water HAL.